2020
DOI: 10.1080/14693062.2020.1822771
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of climate-related risk in Southeast Asia’s power sector

Abstract: Given the growing international pressure to mitigate climate change and increasing fears around climate impacts, current expectations of continued investment in fossil fuels in Southeast Asia's power sector appear puzzling. This paper explores how power sector investors perceive climate-related risks and how they factor these risks into investment decision-making. In doing so, we seek to explain why countries in Southeast Asia are making plans forand investors are continuing to invest inpredominantly fossil fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In addition, recent studies have demonstrated that the presence of a risk management committee whose members possess a deep understanding of environmental issues and their impact on business operations can significantly influence the strategy and transparency in disclosing a company's carbon emissions (Rahman et al, 2023). In this context, the committee is not only responsible for identifying and mitigating environmental risks but also has a role in ensuring that relevant information on carbon emissions is conveyed to stakeholders accurately and consistently (Johnson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies have demonstrated that the presence of a risk management committee whose members possess a deep understanding of environmental issues and their impact on business operations can significantly influence the strategy and transparency in disclosing a company's carbon emissions (Rahman et al, 2023). In this context, the committee is not only responsible for identifying and mitigating environmental risks but also has a role in ensuring that relevant information on carbon emissions is conveyed to stakeholders accurately and consistently (Johnson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, at the employee level, portfolio managers are benchmarked on much shorter-term performance, such as quarterly or monthly 26 . Most climate-related risks are thus way beyond these investment time horizons 28,29 . In a comprehensive survey collecting 436 responses from institutional investors, climate risks were indeed ranked extremely low in comparison to other investment risks 23 .…”
mentioning
confidence: 99%